Analytical and numerical fracture analysis of pressure vessel containing wall crack and reinforcement with CFRP laminates. (June 2018) - Alizadeh, E.; Dehestani, M.
Abstract: This paper concentrates on the analytical and numerical calculation of the critical internal load for a pressure vessel containing a longitudinal edge crack or cracks. Initially, the vessel's capacity is analyzed based on the theoretical fracture methods for seven material properties, different crack lengths, and vessel's wall thickness. Theses analyses are conducted using an extended finite element method (XFEM) to observe its accuracy and applicability. In problems with complex configuration of crack, it's difficult to use theoretical method for analyzing the structure. Therefore, after verifying the XFEM with excellent accuracy, several analyses are made for different cases. By employing the XFEM, the effects of having multiple cracks along the vessel's circumference, crack width along the vessel's wall, crack location on the internal or external edge of the vessel, and applying the FRP laminates to reinforce the vessel are investigated. Besides, the effect of mode II (sliding mode) on behavior of vessel and the elastic-plastic analysis are analytically studied. Results show that the critical internal pressure for a single cracked and a multiple cracked vessel are the same unless two cracks be very close to each other. Increasing the crack width decreases the critical pressure meaningfully. It is also shown that the vessel is more vulnerable to fail by external crack than an internal crack with similar length and width. Also, the cracked bodies are reinforced with FRP laminates which proves that laminates with higher modulus of elasticity have more effect on the critical internal pressure. Moreover, the elastic-plastic analysis does not have significant influence on critical pressure load due to small plastic zone. Highlights: Fracture mechanics of a pressure vessel for different configurations of cracks. Inducing multiple cracks has no effects on the critical internal pressure practically. Greater crack width causes lower critical pressures. External cracks influence more on the vessel's capacity in comparison with internal cracks. Reinforcing laminates with higher modulus of elasticity are more useful for strengthening.